Webinars for Language Teaching: Experience the Essences of the International Seminar Through Internet - Syafrizal Tabi’I Rahman; Rahman Hakim (International Conference on Education and Language (ICEL), 2013)
This article discusses about the result of the investigation on several webinars for English language teaching browsed from the internet as the teaching materials of Seminar on ELT subject in English department of Sultan AgengTirtaysa University. There are three websites of webinars which are chosen by the writers as the sample of webinars.They are 1). Cambridge English Teacher Webinar;2) Pearson ELT Webinars; and 3) Shaping the Way We Teach English Webinar.This research is aimed to find out the way on how to register to the webinars, what kinds of software platform are used for launching the seminar? And How is the interaction between participants and speakers.